2014
DOI: 10.1021/bi5004926
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the HIV-1 Frameshift Element RNA

Abstract: The HIV-1 ribosomal frameshift element is highly structured, regulates translation of all virally encoded enzymes, and is a promising therapeutic target. The prior model for this motif contains two helices separated by a three-nucleotide bulge. Modifications to this model were suggested by SHAPE chemical probing of an entire HIV-1 RNA genome. Novel features of the SHAPE-directed model include alternate helical conformations and a larger, more complex structure. These structural elements also support the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 40 publications
3
35
1
Order By: Relevance
“…3) but mainly differed in whether or not the slippery sequence was base paired. The weak thermodynamic stability of the slippery sequence helix is consistent with formamide titration data (14). Previously, we showed that the anchoring helix modulates frameshifting in vitro, with disruption of this helix causing an increase in frameshifting (6,14).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…3) but mainly differed in whether or not the slippery sequence was base paired. The weak thermodynamic stability of the slippery sequence helix is consistent with formamide titration data (14). Previously, we showed that the anchoring helix modulates frameshifting in vitro, with disruption of this helix causing an increase in frameshifting (6,14).…”
Section: Resultssupporting
confidence: 87%
“…Consistent with this idea, Brakier-Gingras and coworkers found that decreased translation initiation of HIV-1 mRNA resulted in increased frameshifting (13). Additionally, we found that disruption of the genomic secondary structure by mutagenesis led to increased frameshifting in vitro (6,14). SHAPE (selective 2-hydroxyl acylation analyzed by primer extension) data indicate that the genomic secondary structure is remodeled during translation, as regions of the RNA are unfolded and sequestered by the ribosome (14).…”
supporting
confidence: 86%
See 3 more Smart Citations